IMPLEMNETASI NILAI-NILAI PENDIDIKAN ISLAM DALAM PEMBINAAN IBADAH SHOLAT DI SMP UNISMUH MAKASSAR - Mursalin, Mursalin; Miro, Abbas Baco; Pewangi, Mawardi; Malli, Rusli; Sumiati, Sumiati (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2025)
The aim of this research is to describe 1) What the values ​​of Islamic education at Unismuh Middle School Makassar 2) How the values ​​of Islamic education implemented in prayer guidance at Unismuh Middle School Makassar. This research is a qualitative descriptive research. This research examines phenomena and events that occur in the lives of individuals and groups. Data collection instruments through observation and interviews. Data collection techniques consist of data reduction, data presentation, data collection and verification. The research results prove that: 1) Unismuh Makassar Middle School has a strong commitment to integrating the values ​​of Islamic education in every aspect of student life. Through various approaches and strategies, this school strives for students not only to understand, but also to apply religious and moral values ​​in everyday life. The role of teachers in this school is very important, as teachers, role models, mentors and companions in the process of forming student character. They play an active role in conveying Islamic teachings, guiding students in practicing these values, as well as providing moral and spiritual support to students in their journey to understand Islamic values. 2), Coaching is an action and activity that functions to maintain and develop the potential that exists in students so that they can behave better. One of the guidance that needs to be given to students is prayer. In this case, prayer is how students can understand the prayer service. As is done at Unismuh Makassar Middle School, this prayer service is not just a ritual obligation but as a means of educating Islamic values ​​which can be implemented through prayer guidance and educational values. Prayer starts from faith/morals, worship and discipline.